2021
DOI: 10.1371/journal.pone.0256517
|View full text |Cite
|
Sign up to set email alerts
|

Weapon injuries in the crusader mass graves from a 13th century attack on the port city of Sidon (Lebanon)

Abstract: Archaeological excavations close to St Louis’ castle in Sidon, Lebanon have revealed two mass grave deposits containing partially articulated and disarticulated human skeletal remains. A minimum of 25 male individuals have been recovered, with no females or young children. Radiocarbon dating of the human remains, a crusader coin, and the design of Frankish belt buckles strongly indicate they belong to a single event in the mid-13th century CE. The skeletal remains demonstrate a high prevalence of unhealed shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…As a result of the paleopathological examination, the bones found in the area were determined to have belonged to 3 different adult males (Table 3) (15). The lesion seen on the anterior region of the right femur bone in one of these three individuals extends linearly from top to bottom and shows slight bends; it is thought to be a possible piercing injury (Figure 1) (19,20). Upon examining the cut, the person is thought to have died shortly after receiving this blow as no signs of recovery were found.…”
Section: Resultsmentioning
confidence: 96%
“…As a result of the paleopathological examination, the bones found in the area were determined to have belonged to 3 different adult males (Table 3) (15). The lesion seen on the anterior region of the right femur bone in one of these three individuals extends linearly from top to bottom and shows slight bends; it is thought to be a possible piercing injury (Figure 1) (19,20). Upon examining the cut, the person is thought to have died shortly after receiving this blow as no signs of recovery were found.…”
Section: Resultsmentioning
confidence: 96%
“…While burning and destruction of a site does not necessarily indicate intentional violence, it has been observed at other battle sites (Mikulski et al, 2021; Mitchell et al, 2006). Weapons accompanying the remains were also commonly reported (Mikulski et al, 2021; Mitchell et al, 2006). These appear similar to those observed at Kaman‐Kalehöyük, which included a bronze sword on the floor of Room 148 (Omura, 1996) and a spearhead in Room 150 (Omura, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…The healed sharp force trauma on the young adult male from the courtyard is clearly violence‐related because it was caused by a weapon. Healed weapon injuries on individuals from other battle sites may suggest that at least some were professional fighters (Mikulski et al, 2021; Nicklisch et al, 2017) and this could be the case for the individual from the courtyard at Kaman‐Kalehöyük.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to this, relatively few examples of lethal trauma to the cranium have been identified in this region of the eastern Mediterranean, dating to the Hellenistic (see Goldstein et al, 1981), Roman (Nagar, 2003, pp. 127–130), and medieval periods (Mikulski et al, 2021; Mitchell et al, 2006), although numerous other examples have been identified in historical textual sources (Mitchell, 2004, pp. 124–136).…”
Section: Discussionmentioning
confidence: 99%